2007
DOI: 10.1016/j.molbiopara.2007.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Trypanosoma brucei cap hypermethylase Tgs1

Abstract: Many U-snRNAs contain a hypermodified 2,2,7-trimethylguanosine (TMG) cap structure, which is formed by post-transcriptional methylation of an m(7)G cap. At present, little is known about the maturation of U-snRNAs in trypanosomes. The current evidence is consistent with the primary transcript containing an m(7)G moiety, but it is not clear whether the conversion of m(7)G to TMG takes place in the cytoplasm or in the nucleus. To address this issue, we characterized the Trypanosoma brucei homologue of the trimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 22 publications
6
32
0
Order By: Relevance
“…TbMTAP and/or TbMTr1 may be recruited to the SLA1 snoRNA genomic locus as part of a cotranscriptional assembly pathway or join the preformed SLA1 snoRNP. T. brucei Nop10-GFP fusion protein (55) and TbNhp2-TAP tag immunolocalization (65) show accumulation in the nucleolus, consistent with H/ACA snoRNP proteins in other eukaryotic systems. The purification of the TbMTr1 on May 9, 2018 by guest http://mcb.asm.org/ complex in association with nucleolar RNP components required reexamination of TbMTr1 localization.…”
Section: Discussionsupporting
confidence: 70%
“…TbMTAP and/or TbMTr1 may be recruited to the SLA1 snoRNA genomic locus as part of a cotranscriptional assembly pathway or join the preformed SLA1 snoRNP. T. brucei Nop10-GFP fusion protein (55) and TbNhp2-TAP tag immunolocalization (65) show accumulation in the nucleolus, consistent with H/ACA snoRNP proteins in other eukaryotic systems. The purification of the TbMTr1 on May 9, 2018 by guest http://mcb.asm.org/ complex in association with nucleolar RNP components required reexamination of TbMTr1 localization.…”
Section: Discussionsupporting
confidence: 70%
“…Comparisons of Tgs1 family homologies indicate that hypermethylases from lower eukaryotes are mainly composed of the conserved MTase domain, whereas proteins from higher eukaryotes have long N-terminal domains with no obvious similarities to other known proteins (32). Concerning the former class, it has been shown that Tgs1 proteins from Saccharomyces cerevisiae and Trypanosoma brucei are essential for m 3 G cap formation of both snRNAs and snoRNAs (13,33), indicating that the absence of N-terminal regions does not restrict the hypermethylation capabilities of the enzymes. Biochemical studies also showed that S. pombe Tgs1 is a bona fide guanine-specific methyltransferase and that the chemical steps of m 3 G synthesis do not require input from RNA or protein cofactors in vitro (14).…”
Section: Discussionmentioning
confidence: 99%
“…Induction of expression and purification of the N-terminal His-tagged Tgs were carried out as described (25). Protein purity and concentration were evaluated by SDS–PAGE and densitometry using BSA standards and employing ImageJ software.…”
Section: Methodsmentioning
confidence: 99%